Risk factors for intraoperative hypothermia during laparoscopic surgery: A systematic review and meta-analysis - Hao Wang; Alei Wang; Xiaoyan Song; Jianying Luo; Peihong Zhang (PLoS ONE, 2025)
Objectives To systematically evaluate the risk factors for intraoperative hypothermia in patients undergoing laparoscopic surgery globally; and to provide information on how to prevent complications and, should they occur, how to intervene. Methods This study was registered in the International Prospective Register of Systematic Reviews (PROSPERO; No. CRD42024555506). We searched the following databases: PubMed, Cumulative Index of Nursing and Allied Health Literature (CINAHL), Web of Science Core Collection, EMBASE, China National Knowledge Infrastructure (CNKI), and Wanfang. Data on risk factors for hypothermia during laparoscopic surgery were systematically collected through June 1, 2024. After evaluating references that met Newcastle–Ottawa scale (NOS) or Agency for Healthcare Research and Quality (AHRQ) inclusion criteria, we performed a meta-analysis of the extracted data using RevMan version 5.4. Results We included 11 studies with a cumulative sample size of 3550 cases and extracted 14 risk factors. Meta-analysis results showed that age (odds ratio [OR], 1.02; 95% confidence interval [CI], 1.00–1.03; P = 0.04), total amount of intraoperative CO2 injected into the abdominal cavity > 200 L (OR, 1.5; 95% CI, 1.30–1.81; P < 0.001), duration of operation > 120 min (OR, 2.32; 95% CI, 2.03–2.65; P < 0.001), duration of anesthesia > 150 min (OR, 1.55; 95% CI, 1.26–1.92; P < 0.001), intravenous (IV)–fluid volume>1500 mL (OR = 1.77; 95% CI, 1.48–2.12; P < 0.001), and intraoperative blood loss ≥ 150 mL (OR, 1.66; 95% CI, 1.27–2.17; P < 0.001) were risk factors for intraoperative hypothermia. Conclusions We found that age, total amount of CO2 injected into the abdominal cavity during the operation, operation duration, anesthesia duration, IV-fluid volume, and intraoperative blood loss to be risk factors for intraoperative hypothermia in patients undergoing laparoscopic surgery. Given the limitations of the available literature’s quantity and quality, our conclusions should be verified by higher-quality studies.